Component-wise exergy loss analysis under injection timing and EGR variations in a heavy-duty diesel engine - Eihab A. Raouf Mustafa (Teknomekanik, 2026)
This study investigates the component-wise exergy behavior of a heavy-duty diesel engine under combined variations in injection timing and exhaust gas recirculation (EGR). A calibrated Diesel-RK model was used to simulate steady-state operation over a representative speed-load range. Fuel, brake, exhaust, wall heat, and destruction exergy terms were then evaluated using a consistent post-processing framework. The results showed that increasing EGR from 0 to 0.20 reduced the brake exergy fraction from 33% to 14%. In comparison, the destruction fraction increased from 44% to 73%, indicating that dilution intensified combustion-related irreversibility with a greater influence on irreversibility than on wall heat transfer. Across the investigated speed-load range without EGR, destruction typically remained within about 39–45% of fuel exergy. Advancing injection timing shifted heat release toward top dead center and redistributed wall heat exergy from the liner (40% to 26%) toward the piston and cylinder head, with contributions increased to approximately 37–40% each. At high load, moderate advancement improved thermodynamic efficiency, whereas excessive advancement increased wall thermal loading and reduced further gains. At part load, sensitivity increased because combustion duration appeared to influence thermal response more strongly than peak temperature. A limited trade-off region was identified in which exergy efficiency exceeded about 30%, and destruction dropped below roughly 45%, primarily at advanced timing and high load. However, excessive injection advancement resulted in physically infeasible EGR operation due to insufficient exhaust pressure to sustain recirculation flow, thereby defining a practical operating boundary. Injection timing affected not only efficiency but also whether EGR could function, therefore, optimal calibration must balance combustion phasing, dilution-induced irreversibility, and component-level thermal loading.